2021
DOI: 10.1111/jop.13209
|View full text |Cite
|
Sign up to set email alerts
|

Burkitt lymphoma of the head and neck: An international collaborative study

Abstract: Background: Burkitt lymphoma (BL) is an aggressive B-cell lymphoma with three variants (endemic, sporadic, and immunodeficiency-associated), presenting with specific epidemiological and clinical features. Burkitt lymphoma affects the head and neck region (BLHN) in approximately 10% of cases. The aim of this study was to undertake a comparative analysis of the clinicopathologic and immunohistochemical (IHC) features of BLHN diagnosed in patients from Africa, Guatemala, and Brazil. Methods: Cases diagnosed as BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…This could be explained by the fact that NHL includes a wide variety of histological subtypes with different age predilections [ 39 ]. Burkitt lymphoma, for instance, is known to be predominant in infants and young adults [ 40 ]; this was also evident in our study as the youngest age (3.5 years) in the study sample was of a case diagnosed as Burkitt lymphoma. On the other hand, other types of lymphoma, such as DLBCL, are more common in adults.…”
Section: Discussionsupporting
confidence: 75%
“…This could be explained by the fact that NHL includes a wide variety of histological subtypes with different age predilections [ 39 ]. Burkitt lymphoma, for instance, is known to be predominant in infants and young adults [ 40 ]; this was also evident in our study as the youngest age (3.5 years) in the study sample was of a case diagnosed as Burkitt lymphoma. On the other hand, other types of lymphoma, such as DLBCL, are more common in adults.…”
Section: Discussionsupporting
confidence: 75%
“…The authors found a prevalence of BL and the main signs and symptoms were unilateral tonsillar enlargement, alteration in appearance of the tonsil, and cervical lymphadenopathy ( 19 ). Although our study reported few clinical manifestations in the oral and maxillofacial region, it is important to emphasize clinical features such as bone destruction, tooth mobility, ulceration, tooth displacement, and oral bleeding, since they are frequent clinical signs of BL ( 21 ). Other clinical aspects of relevance for the dentist, and which were not reported in this study due to the exclusion criteria, are swelling and gingival bleeding, as these signs need to be carefully evaluated in order to exclude gingival infiltration of leukemia or Langerhans cell histiocytosis ( 15 ).…”
Section: Discussionmentioning
confidence: 88%
“…Thyroglossal cyst (31%), plunging ranula (17%), and lymphangioma (16%) have been the main diagnoses of head and neck masses in children and adolescents ( 20 ). However, it is important to emphasize that rapidly growing masses causing local destruction at presentation are features that should lead to greater suspicion of malignancy ( 12 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the characteristic floating tooth/teeth pattern usually described in cases of Burkitt lymphoma were also found in other lymphoma subtypes. 25,26 This feature however was still most commonly seen in BL. Another noteworthy finding was the presence of bone involvement in cases of plasmablastic lymphoma, as recently described by Nel et al 27 who showed a predilection for the posterior region of the maxilla.…”
Section: Discussionmentioning
confidence: 99%